Julius Goebel papers - Goebel, Julius, 1857-1931.
Correspondence, subject files, printed matter, and other papers relating mainly to Goebel's career as a professor of German language and literature, his removal from the Stanford University faculty, and German-American affairs. Includes Goebel family correspondence.
Lawyer and educator.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Göbel family -- Correspondence; Goebel family -- Correspondence; Stanford University -- Faculty; German Americans; German language -- Study and teaching; German literature -- Study and teaching; Germans -- United States; Educators; Lawyers